Micropillar compression investigation on the mechanical behavior of Ni manufactured using laser powder bed fusion - Li, Shi-Hao (2023)
Micropillar compression tests were performed on unalloyed Ni that was manufactured using the additive manufacturing (AM) technique of laser powder bed fusion (LPBF) with micropillar diameters ranging from 1 to 3.5 μm. In all cases, the single crystalline micropillars with the <110> crystallographic orientation, aligned along the build direction of LPBF and the uniaxial compression axis, are tested. In contrast to other LPBF alloys, in which submicron-scale cellular structures decorated with dense dislocation networks are often reported, only dislocation networks with relatively sparse dislocations along the network boundaries are observed in the LPBF Ni. Results of the micropillar compression tests show that the stress-strain responses of the LPBF Ni in the plastic regime are dominated by pronounced serrations and both the yield strength and work hardening behavior are highly dependent on the pillar diameter. Microscopic observations on the deformed pillars show that that the relatively low-density of dislocations in the microstructure of the LPBF Ni do not offer a substantial resistance to the dislocation motion. This is further verified by comparing the mechanical performance of the micropillars of the LPBF Ni with those of the pre-strained Ni, nanocrystalline Ni and 316L stainless steel manufactured via the directed energy deposition AM technique.